A Comparitive Study on Mongo and Cassandra Database For Data Clustering - Sasikala, R (International Journal of Computer Sciences and Engineering, 2025)
Databases provide data storage, extraction and manipulation by using SQL language. It has emerged as a backend to support Big Data applications. It is mainly characterized by horizontal scalability, schema-free data models, and easy cloud deployment. There are various NoSQL databases and the performance varies with different types based on node capacity, number of cores, replication actor, and different workloads. Hence, it is important to compare them in terms of their performance and verify how the performance is related to the different database. This paper focuses on comparison of Cassandra, MongoDB and HBase which are the most commonly used NoSQL databases. This comparison between NoSQL databases deploys them on yahoo cloud platform which uses different types of virtual machines and cluster sizes to study the effect of different configurations. The final result shows the performance of databases at different workload levels and the result can be compared to find out the best among these two databases. In this paper, the comparison of two data bases which are mongo db and Cassandra db algorithm are used to produce the result which is the best db for future data base